PENGARUH DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR CAMAT LUAHAGUNDRE MANIAMOLO KABUPATEN NIAS SELATAN - Martina Marlina Lase (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
This study aims to determine the effect of work discipline on employee performance in the Luahagundre Maniamolo District Office, South Nias Regency. This type of research is an associative quantitative research. The sample in this study amounted to 30 employees. The analytical method used in this research is simple linear regression analysis. The results of this study indicate that there is a significant influence between work discipline on employee performance in the Luahagundre Maniamolo Sub-district Office, South Nias Regency. In this study, a simple linear regression equation was obtained, namely: Y = 7.750 + 0.860X obtained t count (4.892) > t table (1.701) and a significant level of 0.000 < 0.05. Then the decision is that Ha is accepted, H0 is rejected, meaning that the work discipline variable has a positive and significant effect on employee performance. Then an R Square value of 0.461 or 46.1% is obtained, so it can be concluded that Work Discipline Influences Employee Performance at the Luahagundre Maniamolo Sub-district Office, South Nias Regency.